A Predictor for Decreased Left Ventricular Ejection Fraction in Patients Present to the Emergency Room with Non St Segment Elevation Myocardial Infarction - Almohammadi, Ramzi A. (Cardiology and Cardiovascular Medicine, 2024)
Background: Potassium (K) is a vital electrolyte in medical settings, essential for the maintenance of regular cardiac function. Deviant potassium levels from its normal range may impact the electrical activity of the heart, possibly resulting in arrhythmias and other issues related to the heart. Objective: This study aims to assess the initial potassium level upon arrival of patient with NSTEMI as a predicator for low LVEF. Method: A study analyzed 346 patients with Non-ST Elevation Myocardial Infarction - Acute Coronary Syndrome (NSTEMI-ACS) at King Abdulaziz University Hospital. The study analyzed several parameters such as duration of chest pain, diabetes, age, initial potassium and magnesium levels, LVEF by echocardiography, electrical instability, and treatment plan. Results: Results revealed the first potassium level seems to be a good indicator of low LVEF in people who have had a NSTEMI. Based on our research, lower potassium levels are linked to a higher risk of cardiovascular problems, and this risk rises as potassium levels drop. .